LITERASI KEUANGAN PELAKU INDUSTRI KECIL MENENGAH DI KABUPATEN MAGETAN - Pandoyo Pandoyo; Mohammad Sofyan; Iin Andrayanti (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This study aims to determine the financial literacy of small and medium-sized industry players in the Magetan Regency, which is centralized in the Magetan Regency Promotion House. Data collection techniques through interviews or conversations where interviewers to 60 players in a small and medium industry. Interviews are conducted face-to-face with the informant to be interviewed. The financial literacy aspects studied include (1) aspects of financial knowledge; (2) aspects of financial behavior; (3) aspects of financial attitudes; and (4) aspects of financial capability.  The results showed that from (1) aspects of knowledge, the IKM actors of Magetan Regency have financial behavior by consciously paying taxes, being able to compile financial reports, setting aside funds for unexpected costs, and recording various expenses properly and correctly; (2) aspects of financial behavior, having financial behavior consciously paying taxes, being able to compile financial statements, setting aside funds for unexpected expenses, and recording various expenses properly and correctly; (3) aspects of financial attitudes, Magetan regency IKM actors can manage all financial aspects and have daily books for all expenses; and (4) aspects of financial confidence, Magetan regency IKM actors have a plan and vision where and where the money will be spent, and can record savings balances